DRINK WATER QUALITY AND WATER SUPPLY PROJECTS EFFICIENCY EVALUATION: LABORATORY AND POPULATION HEALTH INDICATORS BASED ON LOCAL ANALYSES - Raximov Baxodir; Sultonov Erkin; G’aybullayeva Aziza; Shonazarova Muxlisa; Boybusinova Aziza; To’rayeva Mohinabonu (Bright Mind Publishing, 2025)
Drink water of quality hygienic evaluation and water supply of projects efficiency world on a scale the most important from factors one divided , population health , epidemiological stability and socio-economic development for directly solution doer role World Health Organization storage According to the World Health Organization (WHO) according to the world according to water with related diseases every 485 thousand per year more than death to the state reason will be , especially drink water low quality in the regions diarrhea , bowel infections , parasitic diseases and especially children between high death level (WHO, 2023) . Also , polluted drink water with related was chemical dangers — nitrates , heavy metals ( lead , arsenic , cadmium ), pesticides and microbiological indicators out of the norm increase — many chronic diseases , that including kidney deficiency , oncological diseases and heart and blood vein diseases the risk noticeable at the level increases (Rahman et al., 2022).